Strategies and Innovations for Enhancing Sustainable Performance in SMEs During The 4.0 Digital Business Era - Fendy Cuandra; Candy Candy (LPPM Universitas Terbuka, 2024)
Purpose – This research aimed to examine the impact of business model innovation (BMI), competitive advantage (CA), learning capability (LC), technological capability (TC), and relational capability (RC) on small and medium-sized enterprises (SMEs) sustainable performance (SP). Additionally, the mediating role of LC in the relationship between TC and RC, as well as the SP of SMEs is explored. Methodology – This research uses primary data obtained from a questionnaire completed by 210 respondents. Purpose sampling which focuses on culinary SMEs is adopted, specifically in Batam City, and has been operating for at least 3 years. Findings – The result showed a significant impact of CA, TC, LC, and RC on the SP of SMEs in Batam City. Furthermore, there is no significant influence from BMI, and LC is identified as a mediating factor in the relationship between TC and SP. Originality – The research reports the latest information and analysis related to factors that can help SMEs maintain their SP. These include the absence of the role of BMI and the discovery of the mediating impact of LC and TC on the SP of SMEs.